Use of a wireless NIRS monitor to track changes in muscle oxygenation for laboratory-based Nordic skiing test protocol - Cornachione, K.; McLaren, J.; Heil, D. P. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The primary purpose of this study was to evaluate this newly developed wireless NIRS monitor as a potential tool for both lab- and field-based crosscountry skiing studies. Specifically, it was of interest to determine the degree to which measures of both Sm02 and THL would vary as a function of exercise intensity, arm versus thigh wearing location, as well as use of compression or non-compression ski clothing. These evaluations were performed in the context of a larger series of studies.